Analisis Framing Berita Politik Menjelang Pilkada Klaten Tahun 2020 pada Solopos.com - Ibrahim Hasan; Fathan Fathan (UIN Raden Mas Said Surakarta, 2020)
Solopos.com as part of the local digital media development for Solopos should be a big information contributor to the public regarding issue activities and political developments of the elite. One year ahead of the 2020 regional election in Klaten, Solopos.com reported the phenomenon of politicizing the agenda of activities in Klaten Regency Government by government officials. For this reason, this study aims to examine how the Solopos.com framing in informing news about politics ahead of the Pilkada in Klaten Regency. The approach in this study was literary qualitative, with the framing analysis of Zhongdang Pan and Gerald M. Kosicki. This analysis shows the construction of the reality of the Solopos.com news framing by promoting the power monitoring function. Solopos.com directed readers that there was a politicization of the agenda of activities in Klaten Regency Government. The ideology of Solopos.com siding with the community over the function of media as social control. Through framing, the objectivity of Solopos.com news was built firmly and shown by reality. Solopos.com media politics in this phenomenon was seen as not neutral because of the lack of balance in the quantity of coverage of the PDIP Political Party with other Political Parties, one of which could be seen through political persuasion over the news of the politicization of the agenda of Klaten Regency Government activities by a pro-incumbent official, Sri Mulyani, who has a PDIP background.